2021
DOI: 10.1016/j.isci.2021.102283
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion G protein-coupled receptor VLGR1/ADGRV1 regulates cell spreading and migration by mechanosensing at focal adhesions

Abstract: Summary VLGR1 (very large G protein-coupled receptor-1) is by far the largest adhesion G protein-coupled receptor in humans. Homozygous pathologic variants of VLGR1 cause hereditary deaf blindness in Usher syndrome 2C and haploinsufficiency of VLGR1 is associated with epilepsy. However, its molecular function remains elusive. Herein, we used affinity proteomics to identify many components of focal adhesions (FAs) in the VLGR1 interactome. VLGR1 is locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 55 publications
12
62
0
Order By: Relevance
“…(2021) N/A Experimental models: organisms/strains Mouse: C57BL/6J (P0 age) The Jackson Laboratory Stock no: 000664 Mouse: Vlgr1 /del7TM (P0 age) Breed on a C57BL/6 background McMillan and White (2004) Mouse: Drum B (P0 age) Breed on a C57BL/6 background Potter et al. (2016) and Kusuluri et al. (2021) Recombinant DNA RFP-Paxillin Rudolf E. Leube, Rick Horwitz Rudolf E. Leube, Rick Horwitz Software and algorithms ImageJ software National Institutes of Health (NIH) http://imagej.nih.gov/ij/download.html Focal adhesion analysis server https://faas.bme.unc.edu Berginski and Gomez (2013) Other Stereomicroscope Leica Microsystems Leica WILD M3B Cold light source Leica Microsystems Schott KL750 Inverted microscope Nikon Instruments Inc. Nikon Eclipse Ti2-E Spinning disc unit Yokogawa Electric Corporation CSU-W1 Leica confocal microscope Leica Microsystems DM6000B Centrifuge Eppendorf Centrifuge 5430 R Medium-sized scissors A. Dumont & Fils Cat#T5074 Dumont #3 curved forceps A. Dumont & Fils Cat#T504 Dumont #4 standard tip forceps A. Dumont & Fils Cat#T505 Dumont #7 standard tip forceps …”
Section: Key Resources Tablementioning
confidence: 99%
See 4 more Smart Citations
“…(2021) N/A Experimental models: organisms/strains Mouse: C57BL/6J (P0 age) The Jackson Laboratory Stock no: 000664 Mouse: Vlgr1 /del7TM (P0 age) Breed on a C57BL/6 background McMillan and White (2004) Mouse: Drum B (P0 age) Breed on a C57BL/6 background Potter et al. (2016) and Kusuluri et al. (2021) Recombinant DNA RFP-Paxillin Rudolf E. Leube, Rick Horwitz Rudolf E. Leube, Rick Horwitz Software and algorithms ImageJ software National Institutes of Health (NIH) http://imagej.nih.gov/ij/download.html Focal adhesion analysis server https://faas.bme.unc.edu Berginski and Gomez (2013) Other Stereomicroscope Leica Microsystems Leica WILD M3B Cold light source Leica Microsystems Schott KL750 Inverted microscope Nikon Instruments Inc. Nikon Eclipse Ti2-E Spinning disc unit Yokogawa Electric Corporation CSU-W1 Leica confocal microscope Leica Microsystems DM6000B Centrifuge Eppendorf Centrifuge 5430 R Medium-sized scissors A. Dumont & Fils Cat#T5074 Dumont #3 curved forceps A. Dumont & Fils Cat#T504 Dumont #4 standard tip forceps A. Dumont & Fils Cat#T505 Dumont #7 standard tip forceps …”
Section: Key Resources Tablementioning
confidence: 99%
“…We recently showed that the adhesion G protein coupled receptor (GPCR) ADGRV1/VLGR1 (very large G protein coupled-receptor-1) is a component of FAs and mutations in VLGR1 cause defects in FA growth and maturation processes ( Kusuluri et al., 2021 ). In the latter study, we used isolated primary BL/6 wild-type astrocytes, Vlgr1 / del7TM mice lacking the seven transmembrane domains (7TM) and the intracellular domain (ICD) of Vlgr1 ( McMillan and White, 2004 ), and mutant Drum B mice in which only a small portion of the N-terminal fragment is present and the entire C-terminal fragment is missing ( Potter et al., 2016 ; Kusuluri et al., 2021 ). A significant decrease in the number and length of FAs was observed in both Vlgr1 mutant mice compared with primary BL/6 wild-type astrocytes ( Figure 10 ) ( Kusuluri et al., 2021 ).…”
Section: Expected Outcomesmentioning
confidence: 99%
See 3 more Smart Citations